2008
DOI: 10.1071/ch08202
|View full text |Cite
|
Sign up to set email alerts
|

Convenient and Efficient Synthesis of Thiol Esters using Zinc Oxide as a Heterogeneous and Eco-Friendly Catalyst

Abstract: A catalytic method was developed to synthesize thiol esters from the reaction of acyl chlorides and thiols using zinc oxide as a catalyst under solvent-free conditions at room temperature. Mild reaction conditions, short reaction time, excellent yields of products and recyclability of the catalyst are noteworthy features of this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is noted that Zn, ZnO, CoCl 2 , and BiCl 3 are active catalysts for the synthesis of some thiol esters with acetyl chloride at room temperature. A large number of experiments were carried out to screen an effective catalyst for the acylation of glutathione with acetyl chloride, and the results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that Zn, ZnO, CoCl 2 , and BiCl 3 are active catalysts for the synthesis of some thiol esters with acetyl chloride at room temperature. A large number of experiments were carried out to screen an effective catalyst for the acylation of glutathione with acetyl chloride, and the results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Under same conditions, in another reports, O-acylation of alcohols and phenols with acid chlorides were carried out using ZnO and nano ZnO. [51][52][53] Bromodimethylsulfonium bromide is an attractive reagent in organic synthesis. In the year of 2005, Khan and his co-workers utilized from this reagent for the acylation of alcohols, phenols, thiols and amines.…”
Section: Solvent-free Acylation Reactionsmentioning
confidence: 97%
“…2 In the Hantzsch condensation, it is reported that lesser reaction time and higher yield is more pronounced, with ZnO nanoparticles. 3 Thus, nano zinc oxide, being a more effective catalyst, is employed in new C-C, C-P, C-N, C-S bond formations via Michael addition reaction 4 , in synthesis of organic carbonates 5 , in Friedel-Crafts acylation [6][7][8] for the synthesis of aromatic ketones, in reaction of acid chlorides with alcohols /thiols / phenols 9 , Friedlander Quinolone synthesis 10, etc. Nano ZnO has also been employed under solvent-free conditions in reactions in which, a higher yield (90 -98 %) has been achieved.…”
Section: Introductionmentioning
confidence: 99%